2009
DOI: 10.1590/s1516-84842009005000084
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da correlação entre os níveis de hemoglobina fetal e o prognóstico dos pacientes com anemia falciforme

Abstract: Estudo da correlação entre os níveis de hemoglobina fetal e o prognóstico dos pacientes com anemia falciformeStudy of the correlation between fetal hemoglobin levels and the prognosis of patients with sickle cell anemia REVISTA BRASILEIRA DE HEMATOLOGIA E H E M O T E R A P I A REVISTA BRASILEIRA DE HEMATOLOGIA E H E M O T E R A P I

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 8 publications
1
7
0
3
Order By: Relevance
“…Studies have shown that this drug leads to increased Hb F levels in approximately 50% of patients with SCD. High Hb F concentrations may decrease the severity of illness because of inhibition in the polymerization of Hb S. Hb F alter contact sites between Hb molecules, impairing polymer formation with consequent reduction in the sickling process (21-23) . This is a potential reduction factor of hemolysis and the consequent cell damage caused by substances released during this process, for example, iron.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that this drug leads to increased Hb F levels in approximately 50% of patients with SCD. High Hb F concentrations may decrease the severity of illness because of inhibition in the polymerization of Hb S. Hb F alter contact sites between Hb molecules, impairing polymer formation with consequent reduction in the sickling process (21-23) . This is a potential reduction factor of hemolysis and the consequent cell damage caused by substances released during this process, for example, iron.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies show an association of the clinical heterogeneity ofSCD with Hb F levels and the intensity of the hemolytic process (3,18,19) . …”
Section: Discussionmentioning
confidence: 99%
“…There is a need to understand the mechanisms responsible for hemoglobin switching, as reversing it can provide major therapeutic benefits to persons affected by ␤ hemoglobinopathies [8]. Individuals with SCA and the CAR haplotype often have HbF levels below 5%, while those with the Benin haplotype show intermediary HbF levels, 5-10% [9,65]. The present study shows that the Bantu haplotype had a greater DI than Benin haplotype.…”
Section: Discussionmentioning
confidence: 56%
“…Genetic characteristics affecting clinical severity include variations in the HbF level, the coexistence of alpha-thalassemia, and the haplotype associated with the HbS gene [5][6][7][8][9][10]. The different haplotypes of SCA are Bantu or Central African Republic (CAR), Benin (BEN), Senegal (SEN), Cameroon, and Arab-Indian.…”
Section: Introductionmentioning
confidence: 99%